Motivation Affects Sports and Life Skills in Physical Disabled People - ÇELENK, Çağrı (2021)
In this study, it has been tried to determine the motivation of participation in sports and the effects of sports on their lifestyles of different physically disabled individuals who do sports and those who do not, and the differences between the types of disabilities were examined. A total of 732 physically disabled individuals including 327 people who do sports and 405 people who do not do sports were included in the study. Personal Information Form, Physical Activity Participation Motivation Scale (PAPMS) and the Effect of Sports on Life Skills Scale (SLSS) were used as data collection tools. There is a statistically significant difference between those who do sports and those who do not in total and all sub-parameters in PAPMS and SLSS (p <0.05). When the total scores and sub-dimensions of the participants are examined, there is a positive correlation between PAPMS and SLSS (p <0.05). When the responses of the participants to FAPMS and SLSS are compared according to the type of disability, there is a statistically significant difference between those who do sports and those who do not in the total and sub-dimensions of Orthopedic, Visually and hearing impaired individuals (p <0.05). As a result, it shows that sports have a positive role in the motivation of participating in physical activities and contribute to life skills on disabled individuals who do sports. It is thought that sports will have a positive effect not only on their participation in physical activities, but also in many cognitive learning processes due to the increase in motivation of people with disabilities and help the disabled person to become more active and accepted in the society.